A facile route to vertically aligned electrospun SnO2 nanowires on a transparent conducting oxide substrate for dye-sensitized solar cells - Krishnamoorthy, Thirumal (2013)
We demonstrate a large-scale production of aligned SnO2 nanofibers with a multi-nozzle electrospinning method combined with an air-shield enclosed rotating drum collector. The production rate by this multi-nozzle approach is several times higher than that of the single-nozzle electrospinning. The nanofibers produced were having a short range of diameters similar to the case of nanofibers produced by single nozzle electrospinning. The well-aligned nanofibers are subsequently processed into vertically oriented SnO2 nanowires on an FTO substrate. The average diameter and length of the wires were 75 ± 25 nm and 19 ± 2 μm, respectively. Dye-sensitized solar cells using this nanostructured material as the working electrode yielded a short-circuit current density (Jsc) of 9.9 mA cm−2 (which is 42% higher than that achieved by nanowires produced by other methods), an open-circuit voltage (Voc) of 0.525 V and a power conversion efficiency (η) of 2.53%. We believe that improvement of the multi-nozzle electrospinning is highly promising for commercialization due to simplicity and easiness of fabricating the spinneret, control over the diameter and spatial orientation of the fibers.